PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN ABDUL’S GROUP SEMARANG - Adi Prakosa; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
In order to achieve company goals better, Abdul's Group. Attributes can determine which ones are appropriate or not appropriate to the needs and desires konsumen.Tipe used explanatory research study with a sample size of 100 respondents was taken using a non probablity sampling with accidental sampling technique. Measurement scale with Likert scale. Data collection by interview using a questionnaire. Analysis of data using simple linear regression and multiple regression test with SPSS 16.0. While testing the hypothesis using the t test, f test, correlation coefficient, and the coefficient of determination. The results showed that prices have an influence on purchasing decisions with 0.618 correlation coefficient and the coefficient of determination of 38.2%, the packaging has an influence on purchasing decisions with 0.533 correlation coefficient and the coefficient of determination 28.4%, the service has an influence on purchasing decisions with a correlation coefficient of 0.823 67.7% and the coefficient of determination, the product quality has an influence on purchasing decisions with a correlation coefficient of 0.644 and a coefficient of determination of 41.5%, and the size has an influence on purchasing decisions with a correlation coefficient of 0.755 and a coefficient of determination of 56.9%, price, packaging , service, product quality, and size together have an influence on purchasing decisions by the equation Y = 1.584 + 0.928 + 4.328 X1 + 3.980 X2 + 1.278 X3 + 1.277 X4 X5. This shows that Abdul's Group has a good service, by having good communication between employees and customers, ketramapilan good The results menunujukan Abdul's Group has a good service in terms of employees' communication skills with customers and employees when describing the product, and has klemahan in terms of packaging, particularly on the security package. Conclusion The study is the product attributes affect purchase decisions. But there are still consumers who stated that the application of pricing, packaging, service, product quality, and size is not good. Advice for Abdul's Group is to maintain the value of the service, and the best Abdul's Group uses packing materials that meet the safety standards for food packaging.